Evaluation of wind tunnel interference on numerical prediction of wheel aerodynamics. Issue 224 (May 2022) - Josefsson, Erik; Hobeika, Teddy; Sebben, Simone
Abstract: For a passenger vehicle, approximately 25% of the total aerodynamic drag originates from the wheels, making the aerodynamics of wheels a significant factor for the overall performance of a vehicle. To understand the complex flow field created by the rotational condition and geometry of these bluff-bodies, numerical simulations are often used. However, computations are frequently performed in domains that replicate open road conditions, differing from the conditions of wind tunnels. Therefore, to properly validate a CFD procedure and to correlate physical tests to numerical results, interference effects of the wind tunnel need to be investigated and their impact on the aerodynamics of wheels analysed and compared to that of open road calculations. In this study, numerical simulations on the DrivAer model were performed using different tyres and rims in both open road conditions and with the inclusion of a detailed model of a slotted walls wind tunnel. The results of the simulations are compared to experimental data, consisting of forces and flow field measurements. It was found that the inclusion of the wind tunnel in the computations improves the prediction of the flow fields, resulting in better prediction of both the absolute drag values and the drag deltas between configurations. Highlights: The drag prediction improves with the wind tunnel geometry in the simulations. The largest discrepancies between domains occur for tyres with lateral grooves. Open road simulations overpredict the drag difference between open and closed rims. The wind tunnel blockage alters separations at the tyre and rim. The ground simulation changes the interaction between the front and the rear wheels.